Prospective Teachers Knowledge About the Air Pollutant Standard Index and Fire Disaster Mitigation - Eddy Noviana; L. N. Firdaus; Hadriana; Sumarno (Jurnal Pendidikan Indonesia, 2023)
The knowledge of prospective elementary school teachers about knowledge of the Air Pollutant Standard Index (ISPU) and forest and land fire disaster mitigation is essential. This study aimed to analyze knowledge of the air pollutant standard index and forest and land fire disaster mitigation of prospective elementary school teachers. The approach in this research is to use quantitative survey research. The population is elementary school teacher candidates, with a total of 3000 and 336 research samples. The variables of this study are the knowledge of elementary school teacher candidates. Research instrument used is a test question instrument made with Google Forms and distributed through social media platforms in the form of What Apps. Analysis of research data using descriptive quantitative. The results showed that the knowledge classification of prospective elementary school teachers regarding the standard index of air pollution and forest fire disaster mitigation based on the geographical location of the origin of the university or college consisted of two categories, namely the excellent category and the moderate category. The conclusions from the study show that knowledge of the standard index of air pollution and disaster mitigation of forest and land fires for elementary school teacher candidates in Riau Province, Indonesia is in the medium category.